2022
DOI: 10.3389/fpls.2022.900870
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Revealing the Potential Mechanism of Low-Temperature Stress in Machilus microcarpa

Abstract: Machilus microcarpa is a rare national tree species in China and possesses important ornamental and ecological value. M. microcarpa can be planted in low-temperature areas, depending on whether its seedlings can withstand the harm. To face this problem, the annual seedlings of M. microcarpa were subjected to five temperature treatments, and eight physiological indicators were measured. Furthermore, comparative transcriptome analysis was performed between M. microcarpa leaves treated at 25°C and −2.8°C. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Glycolysis is intimately related with cold tress ( 28 30 ), and PGK as a key enzyme plays crucial roles in glycolysis ( 43 ). Previous studies indicated that glycolytic genes (e.g., GAPC , PFK , PGM , ENO , and PK ) could be induced by cold stress ( 28 30 ). In this study, we found that TaPGK up-regulated the expression of TaGAPC , TaPGM , TaENO , and TaPK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Glycolysis is intimately related with cold tress ( 28 30 ), and PGK as a key enzyme plays crucial roles in glycolysis ( 43 ). Previous studies indicated that glycolytic genes (e.g., GAPC , PFK , PGM , ENO , and PK ) could be induced by cold stress ( 28 30 ). In this study, we found that TaPGK up-regulated the expression of TaGAPC , TaPGM , TaENO , and TaPK.…”
Section: Discussionmentioning
confidence: 99%
“…PGK is a highly conserved reversible enzyme that catalyzes the conversion of 1,3-bisphosphoglycerate and adenosine diphosphate to 3-phosphoglycerate and adenosine triphosphate in glycolysis and mediates the reverse reaction in gluconeogenesis and the Calvin-Benson cycle (43). Glycolysis is intimately related with cold tress (28)(29)(30), and PGK as a key enzyme plays crucial roles in glycolysis (43). Previous studies indicated that glycolytic genes (e.g., GAPC, PFK, PGM, ENO, and PK) could be induced by cold stress (28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the antenna complex LHCII and photosystems I and II ( Figure 10 ) were observed, which suggests that the photosynthetic machinery may undergo alterations in response to chronic radiation exposure. Downregulated DEGs included ISPE_SOLLC , PUR5_VIGUN , PGL1B_ARATH , FTSI1_ARATH , CHLM_ARATH , and PGKH_WHEAT ( Table 4 ), which are associated with chloroplast development and chlorophyll biosynthesis [ 41 , 42 , 43 , 44 , 45 ]. Decreased expression can be either associated with redox damage of the ETC or developmental changes under chronic irradiation conditions.…”
Section: Discussionmentioning
confidence: 99%